Medicinal plants in periurban backyards: spaces for enhancing biodiversity in São Miguel do Guamá, Pará - Souza, Carlos Natham Machado de (2023)
Even with the growing advance in ethnobotanical studies, the amount of data that inventory the uses and knowledge associated with the biodiversity of medicinal plants existing in urban and periurban backyards in the Amazon region is still incipient. This article aimed to carry out a study of medicinal plants in rural backyards in the municipality of São Miguel do Guamá, Pará, valuing traditional knowledge and contributing to local biodiversity. Semi-structured interviews were carried out with 23 residents, selected by non-probabilistic sampling. The importance index (IVs) and the agreement on the main uses (CUP) were calculated. There were records of 80 medicinal recipes, from the use of 65 species. The most representative families were Asteraceae, Euphorbiaceae, and Lamiaceae. The importance value index was attributed to Melissa officinalis L. and to the agreement of main uses of Alternanthera sp., Melissa officinalis L., Plectranthus neochilus Schltr, and Chenopodium ambrosioides L. The highest values ​​of agreement regarding corrected main uses (CUPc) were from Melissa officinalis L., Cymbopogon citratus (DC.) Stapf., and Alternanthera sp. Flu, fever, and diarrhea were the most prevalent health problems. The community preserves traditional medicine customs in health care and this translates into the way of life of these people and the intense circulation of medicinal plants in the backyards.